Essential competences contribution of the S2-PTE course in Universitas Negeri Yogyakarta to work competence - Djoko Laras Budiyo Taruno; Istanto Wahyu Djatmiko; Samsul Hadi; Nurhening Yuniarti (Jurnal Pendidikan Vokasi, 2023)
This study aims to determine the essential competencies contribution of each vocational course and engineering course in the curriculum to the competence needs of education, training, and engineering work in the electrical power competencies. The research was carried out using a goal-oriented evaluation approach. The object of this research is to the essential competencies of the electrical engineering education Master Program's courses at Universitas Negeri Yogyakarta, including engineering and vocational education courses. Data collection used a questionnaire, then analyzed descriptively. Furthermore, it was presented in the form of categorical data and graphs. The research results show that each essential competence contributes 70.0% to electrical education and training jobs. Referring to the Indonesian National Work Competency Standards, each essential competency contributes more than 66.7%. Thus it can be concluded that the essential competencies of the electrical engineering education Master Program's courses in Universitas Negeri Yogyakarta have contributed to the electricity sector jobs.